Rodents harbouring zoonotic pathogens take advantage of abandoned land in post‐Katrina New Orleans. Issue 9 (1st March 2021) - LaDeau, Shannon L.
Abstract : Leptospirosis is a disease that disproportionately affects impoverished urban communities, but is likely to become more prevalent as changing climate alters flooding regimes. The persistence and transmission of the Leptospira pathogen is reliant on small vertebrate animals, predominantly rodents. In this issue of Molecular Ecology, Peterson et al. demonstrate how changes in rodent diversity and abundances across the complex mosaic of abandonment and recovery investment in post‐Katrina New Orleans can predict zoonotic infection prevalence. Understanding the ecological conditions that support persistence and transmission of zoonotic pathogens in urban ecosystems, where they are most likely to affect humans, is critical to effective monitoring and prevention.